Envelhecimento e equidade em saúde no Brasil - Giacomelli, Giana Silva (2018)
This study aims to analyze the dynamics and evolution of population aging in the states, and health equity among Brazilian elderly. The thesis is based on the current concepts and guidelines for public action against population aging adopted by the World Health Organization, which understands aging as a multidimensional process that influences the most diverse aspects of human life. It is also based on the concept of health equity adopted by WHO, which is instrumented by the Model of Social Determinants of Health. The Index of Population Aging for the Brazilian states determined the analysis of aging in the years 2000 and 2010. To evaluate the Health Equity Index was calculated using data available in the System of Health Indicators and Follow - up of Policies of the Elderly (SISAP - Elderly). The results show that Brazil is in the process of aging population. In 2000, the Aging Index was 28.90, while in 2010 this index was 44.82, representing an evolution of 55.10%. All major Brazilian regions and states show an evolution of population aging. The Health Concentration Indexes found for the different dimensions of the Model of Social Determinants of Health suggest that, in a general analysis, there is no equity in health in Brazil, with the most favorable conditions being more present among older people living in better socioeconomic conditions, while less adequate health conditions are more present among the poorest elderly population. At the most dependent levels of public actions, health inequities among Brazilian elderly are greater, evidencing the need for greater attention of public managers to the challenges arising from the aging process.